Eletroresistividade aplicada ao estudo de água subterrânea no município de Salvaterra-Marajó-Pará - BEZERRA, Cesar Augusto Campos de Alencar (Universidade Federal do Pará, 2014)
A pilot area of 200 Km2 in Salvaterra county along the east edge of Marajo island was selected to make a study of groundwater using electrical resistivity methods. Sixty-five Schlumberger vertical electric soundings and six horizontal Wenner resistivity profiles were made. The sounding data were first interpreted individually with the auxiliary point method, and later reinterpreted in groups using an iterative curve-calculating routine. The results show the range of resistivities in this area vary between 5 and 40000 ohm-m. The aquifer appears to be defined by a sequence of layers with resistivities between 500 and 4000 ohm-m. In this pilot area three favorable sub-areas were delimited, covering about 40% of the area, where the interpreted aquifer thickness is in excess of 20 m and sometimes as great as 80 m. The depht to the top of this aquifer zone varies between 1.3 and 6.6 m in the three sub-areas. The geophysical interpretations were verified by four shallow drill holes (to 20 m). Two of these, located within the favorable sub-areas, showed dominantly sand sediments and the other two, drilled outside the favorable areas, showed much more clay and organic material, but limited amounts of fine sand. Analyses of water samples from many existing wells and of the new drill holes show that, in general, there are no problems with the quality of these shallow groundwaters. The only exceptions are several wells withing 100 m of Marajo Bay which show considerable increases in salinity during the height of the dry season, when the Bay waters also have maximum salinity. The ages and origin of the long oval belts of sand are not known with certaint, but they could be channel sands deposited by an ancient river or distributary of this deltaic region. The results of this research have outlined three large zones of good groundwater potential which will be very important for the agricultural and industrial development of this region.